Máquinas Rising from the Trucks against the Coming of Planes : A Posthumanist Reading of Ernest Hemingway’s For Whom the Bell Tolls - Posti, Joni (My University, 2024)
In this thesis, I study American author Ernest Hemingway’s critically and commercially successful novel For Whom the Bell Tolls (1940) through the theoretical framework of posthumanism. The novel tells the story of an American volunteer in the Spanish Civil War, who is tasked to blow up a bridge with the help of local rebels. My aim is to demonstrate that there is a clear posthumanist consciousness at play in the novel and that it is possible and valuable to study classic literature through this branch of literary criticism. Although posthumanism is a rather new theory, there are already multiple different definitions for it. At its largest scope it is interested in all things beyond humans, despite at times being narrowed down to only concern machines. For the purpose of this thesis, my main focus is on the portrayal of machines, but for a full view of the posthumanist consciousness, I also discuss other manifestations of posthumanism, namely nature and beliefs. My analysis of the novel delineates an abundance of posthuman entities in the prose. I discuss their meaning individually and collectively in detail. In the end, it is apparent that the novel displays a distinct posthuman consciousness on which this study shed new light on, although the book has already been studied extensively. The novel has various dimensions of posthumanism that provide much material for further studies in the future.
Keywords: For Whom the Bell Tolls, Spanish Civil War, posthumanism, posthumanist consciousness, machines, nature, mythology and beliefs